Computer Crimes that Violate Human Rights in Girls, Boys and Adolescents in the Province of Guayas, Ecuador, 2014-2023 - Henríquez Chalen, Rosa Virginia (2023)
The massification of digital systems has various readings, among them the benefits for society, making it possible for activities to be carried out more quickly; another reading has implied that certain criminal acts are generated in the virtual space. The objective of this work is to analyze computer crimes perpetrated against children and adolescents that violate human rights; the problem generated is born from the advancement of technology. This study is developed under the qualitative method, which allows the exploration and compilation of information related to the topic; explanatory research is also used to describe the proposed problem. As a result, it is obtained that the computer crimes that are carried out against children and adolescents generate a severe impact on human dignity; finally, it is determined that on the part of the Ecuadorian State, there are no actions aimed at combating the illegal acts that are committed and executed through computer systems.